2017
DOI: 10.1186/s12864-017-3634-5
|View full text |Cite
|
Sign up to set email alerts
|

Allelic incompatibility can explain female biased sex ratios in dioecious plants

Abstract: BackgroundBiased sex ratios are common among dioecious plant species despite the theoretical prediction of selective advantage of even sex ratios. Albeit the high prevalence of deviations from even sex ratios, the genetic causes to sex biases are rarely known outside of a few model species. Here we present a mechanism underlying the female biased sex ratio in the dioecious willow species Salix viminalis.ResultsWe compared the segregation pattern of genome-wide single nucleotide polymorphism markers in two cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Understanding the causes of sex ratio bias in dioecious plants populations is an open question of considerable interest in ecology and evolutionary ecology (Field et al 2013). These results further reinforce the idea that early-acting genetic factors are likely a primary determinant of female-biased sex ratios observed in Salix populations worldwide (Ueno et al 2007, Myers-Smith and Hik 2012, Che-Castaldo et al 2015, Pucholt et al 2017.…”
Section: Effects Of Sex-biased Herbivory Were Limitedsupporting
confidence: 84%
“…Understanding the causes of sex ratio bias in dioecious plants populations is an open question of considerable interest in ecology and evolutionary ecology (Field et al 2013). These results further reinforce the idea that early-acting genetic factors are likely a primary determinant of female-biased sex ratios observed in Salix populations worldwide (Ueno et al 2007, Myers-Smith and Hik 2012, Che-Castaldo et al 2015, Pucholt et al 2017.…”
Section: Effects Of Sex-biased Herbivory Were Limitedsupporting
confidence: 84%
“…Notably, the gender segregation rate in the analysis of the pedigree indicates that the sex of the willow is dominated by a single locus. This finding is consistent with the findings of earlier studies [29,43,44]. Therefore, willows provide a unique system for exploring sex effects.…”
Section: Sex Ratiossupporting
confidence: 92%
“…The bias is partly attributed to the differential feeding of herbivores [26] and the lower viability of males [27]. Recent studies reported that gender bias is related to sex-biased genes [28,29]. Thus far, the underlying reasons behind the predominance of females in Salix populations have not been determined in the literature.Salix suchowensis and Salix triandra are shrub willows distributed in central and northern China, respectively.…”
mentioning
confidence: 99%
“…Our W chromosome assembly has helped explain why sex association analyses sometimes detect multiple unlinked loci on different chromosomes [18,22,28]. GWAS with a nearly exhaustive collection of W contigs in the reference genome yields a single sex association peak (Additional File 2: Figure S2).…”
Section: Discussionmentioning
confidence: 99%